Automation in Computer-Aided Cryptography: proofs, attacks and designs - Barthe, Gilles; Grégoire, Benjamin; Kunz, César; Lakhnech, Yassine; Zanella-Béguelin, Santiago (2nd International Conference on Certified Programs and Proofs, CPP 2012, 2012)
CertiCrypt and EasyCrypt are machine-checked frameworks for proving the security of cryptographic constructions. Both frameworks adhere to the game-based approach to provable security, but revisit its realization from a formal verification perspective. More specifically, CertiCrypt and EasyCrypt use a probabilistic programming language pWHILE for expressing cryptographic constructions, security properties, and computational assumptions, and a probabilistic relational Hoare logic pRHL for justifying reasoning in cryptographic proofs. While both tools coincide in their foundations, they differ in their underlying technologies: CertiCrypt is implemented as a set of libraries in the Coq proof assistant, whereas EasyCrypt uses a verification condition generator for pRHL in combination with off-the-shelf SMT solvers and automated theorem provers. Over the last six years, we have used both tools to verify prominent examples of public-key encryption schemes, modes of operation, signature schemes, hash function designs, zero-knowledge proofs. Recently, we have also used both tools to certify the output of a zero-knowledge compiler.